2017
DOI: 10.1111/jvs.12573
|View full text |Cite
|
Sign up to set email alerts
|

Scaling α‐ and β‐diversity: bryophytes along an elevational gradient on a subtropical oceanic Island (La Palma, Canary Islands)

Abstract: Questions We addressed three questions: (1) what is the variation of α‐ and β‐diversity of bryophyte communities across spatial scales in an elevational gradient; (2) is spatial variation characteristic of different phylogenetic (mosses/liverworts) and/or ecological groups (terrestrials/epiphytes); and (3) what is the contribution of species richness and species replacement (true turnover) to β‐diversity along the elevational gradient? Location La Palma, Canary Islands, Spain. Methods An elevational transect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…2 ). Some studies on bryophytes performed in warmer climate zones found a hump-shaped relation of richness to elevation 56 , 57 . However, in the temperate zone, an increase of richness with elevation for lichens and bryophytes was found also by Nascimbene and Marini 27 and Spitale 28 who explained their results with a negative relationship of richness with temperature and associated conditions such as slower evaporation rates.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Some studies on bryophytes performed in warmer climate zones found a hump-shaped relation of richness to elevation 56 , 57 . However, in the temperate zone, an increase of richness with elevation for lichens and bryophytes was found also by Nascimbene and Marini 27 and Spitale 28 who explained their results with a negative relationship of richness with temperature and associated conditions such as slower evaporation rates.…”
Section: Resultsmentioning
confidence: 99%
“…The fieldwork was conducted from April 2012 to April 2013. The sampling design followed BRYOLAT methodology [32,33,34,35]. Within each site we studied: plots, subplots and microplots.…”
Section: Methodsmentioning
confidence: 99%
“…Hernandez‐Hernandez et al. () recently examined richness and turnover patterns of bryophytes at multiple spatial scales along an altitudinal gradient in the Canary Islands, but neither addressed the effect of grain size on turnover patterns, nor explored the scale dependence of environmental and geographical control on such patterns.…”
Section: Introductionmentioning
confidence: 99%